Nietzsche e Sartre:: a má-fé como performance da vontade ascética - Landim, Robione Antonio (2022)
Under the light of the genealogical method, the present article seeks to establish a link between bad faith and the ascetic will. The latter is visualized through the figure of the priest, which is discussed in the third dissertation of the Genealogy of Morals. Besides representing the old character of religion, the priest is the embodiment of the ascetic will that longs to be otherwise. We hypothesize that this is also the will that is realized in the practice of bad faith. Therefore, this conduct is characterized as a denial, a flight from what one is; it denies the condition of being that carries in itself, the nothingness, in view of transcendence. To approach this theme, we will delimit our reading from the third dissertation of the Genealogy of Morals and from the second chapter of the first part of The Being and Nothingness, but without confining ourselves to these texts. We will first present what the genealogical procedure consists of; then, we will deal with the ascetic will which is embodied by the figure of the priest; and, finally, we will explain the bad faith as a performance of the ascetic will.